Theoretical and practical aspects of innovation policy planning (the case of Estonia) - Р. Линнас (Вестник ВГУ. Серия: Экономика и управление, 2008)
This case study article treats theoretical and practical aspects of planning of innovation policy based on the case of Estonia. The aim of this particular article is to give an overview of substantial theoretical and practical factors of success or failure of innovation policy implementation process, particularly focusing on peculiarities of planning of innovation policy in Estonia. Estonia's case is respectable and intriguing case for research, because the Republic of Estonia has been able to achieve fast and outstanding economic success during the relatively short period of re-independence, does have Skype, the genome project, e-government, m-services etc, but 'shine of success' is going to disappear. Estonia's capacity of international competition is still suffering because of the small size of the economy, technological backwardness, weak international market position, management mistakes, and weak capital structure. Author is in general opinion that it is very difficult to find arguments to claim that Estonia will be successful in implementing innovation policy, as the planning process was not very much similar to the generally accepted model of policy planning process...